ANALISIS NILAI QUIS DAN NILAI PRAKTIK DALAM MENINGKATKAN NILAI UAS (STUDI KASUS KELAS 12.1G.25 AMIK BSI SEMESTER GANJIL 2013/2014) - Supardjijo, . (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2014)
Accounting for a trading company is the subject of the course and Basic Accounting Practices (code 943). Its main activity is the trading company to buy goods (finished products) and sell it back to consumers. Operational trading company include: purchase, spending money, sales, and cash receipts. The subject of trade accounting firm presented at the meeting of the ninth to the fourteenth and ends with final exams (UAS). Presentation materials trading company accounting discussion, in five meetings, namely: (i) the general journal and special journals, (ii) a subsidiary ledger, general ledger and trial balance, (iii) adjusting entries, (iv) the work sheet, and (v ) the financial statements and the final stages of preparation of the financial statements.Semester GPA (IPS) is a combination of the 10%, 20% assignments, midterms (UTS) 30%, and final exams (UAS) 40%. In an effort to increase the value of UAS students 12.1G.25 Class AMIK BSI odd semester 2013/2014, researchers gave the task in the form of quiz and practice.Case study analysis quis value and value in the practice of increasing the value of the framework UAS relationship between X1 (value quis) and X2 (the value of practice) in increasing Y (value UAS), which is formulated Y '= a + b1X1 + b2X2. Descriptive analysis using the computer program SPSS for Windows version 17.0. The results found the regression equation Y = 20.894 + 0.054X1 + 0.227X2 Keywords: midterms, final exams, a cumulative grade point